Effect of TAVR generation on conduction abnormalities – is newer always better?. (3rd October 2022) - Masoudian, B A; Azzu, M; Mihkli, E; Vincent, A; Shaukat, J; Speight, M; Fearon, W; Liang, D
Abstract: Objective: Transcatheter aortic valve replacement has become an established approach to treat severe symptomatic aortic stenosis in patients of all risk levels. Development of conduction abnormality and the need for a permanent pacemaker are known complications of TAVR. The introduction of third generation valves with cuffs has resulted in a significant decrease in post-deployment perivalvular regurgitation. However, there is concern for an increase in development of a new onset left bundle branch (LBBB) and the need for permanent pacemaker (PPM) implantation. This study aimed to identify whether newer valve generations along with the move away from transesophageal echocardiography (TEE) guidance for valve deployment is associated with changes in frequency of conduction block. Methods: 601 consecutive patients who underwent transfemoral TAVR implantation with a balloon expandable valve in a native aortic valve at a single institution from July 2009 to March 2019 were included in the study. 40 patients with LBBB and 91 patients with pacemakers prior to TAVR were excluded from the LBBB analysis. Multivariate logistic regression was used to test for significance. Results: New LBBB occurred significantly more frequently with the newer generation valves, 1st Gen 2/104 (1.9%), 2nd Gen 9/88 (10.2%), 3rd Gen 33/278 (11.9%) (p<0.01). There was no statistically significant increase in pacemakers across valve generations, 1st Gen 7/113 (6.2%), 2nd Gen 7/92 (7.6%), 3rd Gen 30/305 (9.8%). Use of TEE guidance had no effect on either LBBB or pacemaker. There was a strong trend (p=0.057) toward need for pacemaker as larger valves where used, with OR of pacemaker relative to 29 mm valve for 23 mm valve of 0.26 and for 26 mm valve of 0.63. Conclusion: Newer TAVR valves, although beneficial in reducing perivalvular regurgitation, increases the risk of LBBB, without increasing risk need for pacemaker, suggesting possibly different mechanisms for the two complications. Understanding the mechanism for avoiding these complications may be important to avoiding them, as we move to a lower risk population where complication free results are even more important. Funding Acknowledgement: Type of funding sources: None.